Efficacy of Two Alternate Vaccines Based on Plasmodium falciparum Merozoite Surface Protein 1 in an Aotus Challenge Trial - Stowers, Anthony W. (American Society for Microbiology, 2001)
In an attempt to produce a more defined, clinical-grade version of a vaccine based on Plasmodium falciparum merozoite surface protein 1 (MSP1), we evaluated the efficacy of two recombinant forms of MSP1 in an Aotus nancymai challenge model system. One recombinant vaccine, bvMSP1(42), based on the 42-kDa C-terminal portion of MSP1, was expressed as a secreted protein in baculovirus-infected insect cells. A highly pure baculovirus product could be reproducibly expressed and purified at yields in excess of 8 mg of pure protein per liter of culture. This protein, when tested for efficacy in the Aotus challenge model, gave significant protection, with only one of seven monkeys requiring treatment for uncontrolled parasitemia after challenge with P. falciparum. The second recombinant protein, P30P2MSP1(19), has been used in previous studies and is based on the smaller, C-terminal 19-kDa portion of MSP1 expressed in Saccharomyces cerevisiae. Substantial changes were made in its production process to optimize expression. The optimum form of this vaccine antigen (as judged by in vitro and in vivo indicators) was then evaluated, along with bvMSP1(42), for efficacy in the A. nancymai system. The new formulation of P30P3MSP1(19) performed significantly worse than bvMSP1(42) and appeared to be less efficacious than we have found in the past, with four of seven monkeys in the vaccinated group requiring treatment for uncontrolled parasitemia. With both antigens, protection was seen only when high antibody levels were obtained by formulation of the vaccines in Freund's adjuvant. Vaccine formulation in an alternate adjuvant, MF59, resulted in significantly lower antibody titers and no protection.